The Strategy of PAI Teachers in Implementing Gamification Based Learning Methods at SD Ibnu Katsir Berau - Ardiansyah, Ardiansyah; Syauqi S, Ahmad; Mardiana, Dina (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This research aims to analyze the strategies of Islamic Religious Education (PAI) teachers in implementing gamification-based learning methods at Ibnu Katsir Elementary School in Berau. Gamification has emerged as an innovative solution to address the often-perceived theoretical and unengaging nature of Islamic Religious Education (PAI) for elementary school students. This descriptive qualitative research involved PAI teachers and students as participants, with data collected thru observation, in-depth interviews, and documentation. Data analysis included data condensation, data presentation, and drawing conclusions. The research results indicate that PAI teachers developed a systematic planning strategy including content analysis, selection of gamification elements (blessed points, levels, badges, leaderboards, quests, instant feedback), learning scenario design, and preparation of manual media. Implementation is carried out thru tiered memorization games, worship simulations, noble character missions, and story adventures. The challenges faced include technological limitations, complex classroom management, balancing fun and learning, and differing student abilities, which are overcome thru creative adaptation and differentiated gamification. Gamification has proven effective in increasing students' motivation, cognitive understanding, affective character, and psychomotor skills. This research contributes to the development of a contextual gamification model for Islamic Religious Education (PAI) learning in schools with limited resources.